Intralesional triamcinolone acetonide versus platelet rich plasma: a comparative study in the treatment of alopecia areata of scalp - Ranpariya, Rahul H.; Gupta, Sanjeev B.; Deora, Mahendra S.; Agrawal, Prachi V.; Mathur, Rachita; Raheja, Aishwarya (International Journal of Research in Dermatology, 2019)
Background: Alopecia areata (AA) is a chronic inflammatory disease characterized by nonscarring hair loss involving any hair-bearing surface of the body. The current therapy for AA is not curative but rather aimed at controlling or limiting the pathogenic process. Corticosteroids are the most popular drugs used, however localized atrophy is a common complication, particularly with triamcinolone. Promoting hair growth by application of autologous blood extracted platelet rich plasma (PRP) is a simple, yet effective procedure. The aim of the study was to evaluate and compare the efficacy of intralesional triamcinolone acetonide (5 mg/ml) with intralesional PRP in the treatment of two different scalp AA patches of same individual. Methods: A total of 30 patients having ≥2 patches of AA were randomized and given two separate modalities of treatment in two different patches and divided in Group I, treated with intralesional triamcinolone acetonide (5 mg/ml) and Group II, treated with PRP. Interval time between every follow-up was 3 weeks and four such follow-ups were done. Hair regrowth was calculated according to Mac Donald Hull and Norris grading system at every follow-up and was compared with the initial grading. Results: Group I patches, treated with triamcinolone acetonide have the significantly higher mean grading score than the group II patches, treated with PRP at each follow up. Conclusions: Intralesional triamcinolone acetonide is more efficacious than intralesional PRP in the treatment of scalp alopecia areata with no recurrences and very few adverse effects like atrophy and hypopigmentation.